Long-distance transport of per- and polyfluoroalkyl substances (PFAS) in a Swedish drinking water aquifer. (15th October 2022) - Sörengård, Mattias; Bergström, Sofia; McCleaf, Philip; Wiberg, Karin; Ahrens, Lutz
Abstract: Use of per- and polyfluoroalkyl substance (PFAS)-containing aqueous film-forming foams (AFFF) at firefighting training sites (FFTS) has been linked to PFAS contamination of drinking water. This study investigated PFAS transport and distribution in an urban groundwater aquifer used for drinking water production that has been affected by PFAS-containing AFFF. Soil, sediment, surface water and drinking water were sampled. In soil ( n  = 12) at a FFTS with high perfluorooctane sulfonate (PFOS) content (87% of ∑PFAS), the ∑PFAS concentration ( n  = 26) ranged from below detection limit to 560 ng g −1 dry weight. In groundwater ( n  = 28), the ∑PFAS concentration near a military airbase FFTS reached 1000 ng L −1 . Principal component analysis (PCA) identified the military FFTS as the main source of PFAS contamination in drinking water wellfields >10 km down-gradient. Groundwater samples taken close to the military FFTS site showed no ∑PFAS concentration change between 2013 and 2021, while a location further down-gradient showed a transitory 99.6% decrease. Correlation analysis on PFAS composition profile indicated that this decrease was likely caused by dilution from an adjacent conflating aquifer. ∑PFAS concentration reached 15 ng L −1 (PFOS 47% and PFHxS 41% of ∑PFAS) in surface river water ( n  = 6) and ranged between 1 ng L −1 and 8 ng L −1 (PFHxS 73% and PFBS 17% of ∑PFAS) in drinking water ( n  = 4). Drinking water had lower PFAS concentrations than the wellfields due to PFAS removal at the water treatment plant. This demonstrates the importance of monitoring PFAS concentrations throughout a groundwater aquifer, to better understand variations in transport from contamination sources and resulting impacts on PFAS concentrations in drinking water extraction areas. Graphical abstract: Image 1 Highlights: PFAS-contamination of drinking water aquifer impacted by a firefighting training site. PFAS fingerprint analysis can be used to trace PFAS sources. Long-distance transport of PFAS in a drinking water aquifer. Mitigation measures at the firefighting training sites are needed.